ICTV Virus Taxonomy Profile: Pleolipoviridae - Bamford, Dennis H; Pietilä, Maija K; Roine, Elina; Atanasova, Nina S; Dienstbier, Ana; Oksanen, Hanna M; Ictv Report Consortium (The Journal of general virology, 2017)
Members of the family Pleolipoviridae (termed pleolipoviruses) are pseudo-spherical and pleomorphic archaeal viruses. The enveloped virion is a simple membrane vesicle, which encloses different types of DNA genomes of approximately 7-16 kbp (or kilonucleotides). Typically, virions contain a single type of transmembrane (spike) protein at the envelope and a single type of membrane protein, which is embedded in the envelope and located in the internal side of the membrane. All viruses infect extremely halophilic archaea in the class Halobacteria (phylum Euryarchaeota). Pleolipoviruses have a narrow host range and a persistent, non-lytic life cycle. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the taxonomy of the Pleolipoviridae which is available at www.ictv.global/report/pleolipoviridae.
Keywords: Pleolipoviridae; Viral Proteins; fyziologie virů; Virus Physiological Phenomena; viry; taxonomy; genom virový; hostitelská specificita; Halorubrum pleomorphic virus 1; ICTV; Viruses; Host Specificity; Genome, Viral; virové proteiny